2019
DOI: 10.1038/s41598-018-37044-1
|View full text |Cite
|
Sign up to set email alerts
|

Cell force-mediated matrix reorganization underlies multicellular network assembly

Abstract: Vasculogenesis is the de novo formation of a vascular network from individual endothelial progenitor cells occurring during embryonic development, organogenesis, and adult neovascularization. Vasculogenesis can be mimicked and studied in vitro using network formation assays, in which endothelial cells (ECs) spontaneously form capillary-like structures when seeded in the appropriate microenvironment. While the biochemical regulators of network formation have been well studied using these assays, the role of mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 59 publications
5
78
0
Order By: Relevance
“…When ROCK is inhibited, MLCK may still be capable of inducing sufficient contraction of the hydrogel to counteract the Y27632‐mediated inhibition. A recent study showed that when HUVECs grown on hydrogel matrices were treated with Y27632 and blebbistatin, the cells tended to adhere more to the matrix and led to reduced interaction between neighboring cells, and thus less networks formed (Davidson, Wang, Zaimi, Jayco, & Baker, ). All this suggests that cell‐mediated contractile forces are important for vascular network formation.…”
Section: Discussionmentioning
confidence: 99%
“…When ROCK is inhibited, MLCK may still be capable of inducing sufficient contraction of the hydrogel to counteract the Y27632‐mediated inhibition. A recent study showed that when HUVECs grown on hydrogel matrices were treated with Y27632 and blebbistatin, the cells tended to adhere more to the matrix and led to reduced interaction between neighboring cells, and thus less networks formed (Davidson, Wang, Zaimi, Jayco, & Baker, ). All this suggests that cell‐mediated contractile forces are important for vascular network formation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15–24 ] For example, Davidson et al found that networks of contractile endothelial cells with different morphologies could be generated by varying the extent to which cells were able to physically reorganize surrounding ECM fibers. [ 25 ] Brownfield et al also found that mammary epithelial organoids reorganize and align collagen I fibers through cell contractility, and form multi‐cellular protrusions that follow preferentially along the axis of ECM alignment. [ 26 ] However, in neither example was the resulting cell network geometry spatially designed or predictable.…”
Section: Figurementioning
confidence: 99%
“…At high pre-existing fibre densities (like in a conventional collagen I gel) cells stay unorganized. At lower densities of pre-formed fibres (but still the right stiffness of the gel), endothelial cells have recently been shown to align to these fibres (9). At a low cell density, we make a similar observation on collagen: cells align to preformed fibres.…”
Section: Discussionmentioning
confidence: 99%
“…This has, to date, largely been ascribed to shear stress exerted via blood flow (5). However, there are also numerous reports showing that endothelial cells respond to biophysical confinements (6), matrix stiffness (7, 8), and fibrous topography (9, 10). Furthermore, endothelial cells are able to deform collagen I gels (11) and thereby to communicate mechanically (12).…”
Section: Introductionmentioning
confidence: 99%